Behavior Among Parents of Children With Hearing Loss: Analysis Specific to Emotional and Behavioral Disorder Children: The Impact of Social Barriers on the Behavior of Parents of Children with Hearing Loss (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper deals with an analysis of behavior among parents of childrenwith hearing loss. Deaf children are known to be at much greater risk ofdeveloping mental health problems than their hearing peers. A lack ofopportunity to participate in social life resulting from barriers within theenvironment (e.g. language and communication, and social attitudes towardsdeafness) is regarded as major determinants of deaf children’s social andemotional development.